2016
DOI: 10.1094/mpmi-03-16-0048-r
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light Perception by Both Roots and Rhizobia Inhibits Nodule Formation in Lotus japonicus

Abstract: *The e-Xtra logo stands for "electronic extra" and indicates that twelve supplementary figures and one supplementary table are published online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Light represses nodulation in many legumes, and this repression is influenced by the quantity and quality of light (106). For the symbiosis between Mesorhizobium loti and Lotus japonicus, nodule numbers are reduced on blue light-exposed roots as compared to on shaded roots, but not on red light-exposed roots (101). Reduced nodulation correlates with fewer infection threads, possibly due to blue light inhibiting bacterial growth and reducing cell numbers for infection thread initiation.…”
Section: Lov Proteins In Rhizobium Leguminosarum Bv Viciaementioning
confidence: 99%
“…Light represses nodulation in many legumes, and this repression is influenced by the quantity and quality of light (106). For the symbiosis between Mesorhizobium loti and Lotus japonicus, nodule numbers are reduced on blue light-exposed roots as compared to on shaded roots, but not on red light-exposed roots (101). Reduced nodulation correlates with fewer infection threads, possibly due to blue light inhibiting bacterial growth and reducing cell numbers for infection thread initiation.…”
Section: Lov Proteins In Rhizobium Leguminosarum Bv Viciaementioning
confidence: 99%
“…1a and b). However, although the root nodule number of L. japonicus unshaded roots was drastically decreased compared with that of the shaded roots (shaded; 4.11 § 0.20 vs. unshaded; 1.76 § 0.21) 4 , the number of nodules developed on S. rostrata unshaded roots was slightly, but significantly increased, compared with the shaded roots (Fig. 1c).…”
mentioning
confidence: 91%
“…We recently reported that root nodulation of Lotus japonicus, a model legume, was inhibited by white light irradiation, and that the inhibition of nodulation is caused by blue light perception by both the host plant roots and the rhizobia. 4 Moreover, blue light exposure to L. japonicus roots resulted in reduced nodule weight and decreased acetylene reduction activity (ARA). Higher plants are known to develop avoidance mechanisms, such as root negative phototropism 4,5 and the shade avoidance syndrome, 7 to survive under conditions of biotic or abiotic stress.…”
mentioning
confidence: 99%
See 2 more Smart Citations